An Orthodontıc Treatment Approach In Only Maxıllary Dental Arch - Eray Erdoğan (Galenos Yayinevi, 1996)
The affective orthodontic approaches realized rapidly with simple appliances is preferable in clinical practice. The orthodontic mechanics can be planned for just upper arch where there is no orthodontic problem in the lower arch. In this study, the treatment methods in two cases presented in the orthodontic clinic for the correction of their high positioned upper right cuspids. The major orthodontic problems of upper dental arch caused by maxillary transversal discrepancy and early deciduous tooth loses were solved with a combination of modified "Minned-expander" and straight wire sliding mechanics with the brackets having diffrent slot dimensions on the anterior and posterior teeth. The measurements on the basillary radio-graphs showed 66% of skeletal and 34% of dental expantsion after the modified "Minne-expander" therapy fabricated on the posterior bite blocs having molar tubes. In the second case being more severe compared to the other, after this expansion therapy, unilaterally activated transpalatal bar and sliding mechanics with intermaxillary elastics were realized to have a good control of the 5.5 mm of deviated midline that 3mm was corrected by the midpalatal expansion and to increase the distalization of upper left posterior segments. A thermoplastic anchorage appliance that the patient could wear the intermaxillary elastics was used in the lower arch. The orthodontic treatment was completed with no loss of anchorage. The acceptable results gained to solve the major orthodontic problems though the uncompleted academic critters in the finishing of the cases due to the lack of reciprocal tooth movement, conclude the possibility of using this approach in clinical practice for the indicated cases after a good diagnosis and treatment plan.